PENYEMBUHAN LUKA DENGAN PENURUNAN ERITEMA PADA TIKUS PUTIH (Rattus norvegicus) YANG DIBERIKAN GETAH BATANG JARAK CINA (Jatropha multifida L.) - Rinawati; Agustina, Rismia; Suhartono, Eko (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2015)
Wound healing is a process of damaged tissue repair while inflammation is the initial response towound, which is characterized by the presence of erythema and the wound closure. The purpose ofthis study was analyzed the correlation between the wound healing and the reduction of erythema inwhite rats administered with the sap ofJatropha multifida L. stem. This study was true experimental,using Randomized Posttest Only Control Design with Simple Random Sampling technique. Thesamples were 42 rats divided into 14 groups, each of which consisted of 3 rats. The reduction of thewound length was measured using a ruler, and reduction of the erythema was assessed using theprogram of Corel PhotoPaint X5. The average time for the wound length to reduce was on the fourthday, and the average acceleration of erythema reduction was 33.65. The data of the wound lengthreduction were analyzed using the Spearman Correlation test, indicating that p = 0.005. The data oferythema reduction were analyzed using nonlinear regression test, resulting in the value of p = 0.191(p-value > 0.05). It can therefore be concluded that there was a correlation between theadministration of the sap of Jatropha multifida L. stem and the reduction of wound length, but therewas no correlation between the administration of the sap of Jatropha multifida L. stem and thereduction of erythema in white rats (Rattus norvegicus) with contaminated wounds.